IDEOLOGICAL THREATS THAT ENDANGER YOUTH - Toshev Suhrob Mirzaqulovich (Web of Journals Publishing, 2025)
This article provides information about the emergence of ideological threats to young people, as well as ways to prevent these threats and protect young people in society from them.
Keywords: Internal threat, idea, virtual world, ideology, youth immunity, globalization, drug trafficking, patriotism, national identity, dependence, national values.